The Effect of Heat Input on the Tensile Strength and Toughness of welded SS400 Materials by SMAW - Syukran Syukran; Alvi Syahri; Adi Saputra Ismy; Al Fathier Al Fathier; Fadhlurrahman Fadhlurrahman; Amrizal Amrizal (Politeknik Negeri Lhokseumawe, 2023)
Joint materials using welding require the correct stages, starting from the design stage to the processing stage. The design stage starts from the selection of the type of welding, to the selection of the seam angle used. Meanwhile, at the processing stage, the current strength will be selected according to the processing position. The purpose of this study was to determine the effect of welding heat input on the mechanical strength of SS-400 steel in SMAW welding. In this study the material used was SS-400 with current variations of 90 A and 100 A. The results showed that the welding current affected the tensile strength and toughness of the material. The welding current of 100 A has the highest tensile strength and toughness, and then 90 A which has the lowest tensile strength and toughness, while the strain that occurs at current 90A is 13.53%, and the strain that occurs at current 100 A is 12.07%.